2017
DOI: 10.1080/00365521.2017.1339825
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cytokines and inflammatory biomarkers during infliximab induction therapy and the impact of inflammatory burden on primary response in patients with Crohn’s disease

Abstract: In this intensively sampled cohort of Crohn's disease patients, we demonstrate that inflammatory burden is more determining for primary non-response than drug exposure or immunogenicity. Our findings furthermore suggest that the contribution of TNF in inflammation might be higher in primary non-response, contradicting the non-TNF-driven concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…However, no prior studies regarding sequential changes in the actual tissue concentration of TNF‐α and the complex are known, thus we examined previously reported results showing the concentration in serum. Previous studies have reported that the serum concentration of TNF‐α was increased after infliximab therapy in patients with Crohn's disease (Billiet et al, ; Candon et al, ; Cornillie et al, ; Eder et al, ; Ogawa, Matsumoto, Esaki, Torisu, & Iida, ), as well as in those with rheumatoid arthritis (RA) (Charles et al, ; Cuchacovich et al, ) and juvenile idiopathic arthritis (JIA) (Levalampi et al, ). Furthermore, the serum concentration of TNF‐α has also been shown to be positively associated with both the dose and the serum concentration of infliximab (Candon et al, ; Charles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no prior studies regarding sequential changes in the actual tissue concentration of TNF‐α and the complex are known, thus we examined previously reported results showing the concentration in serum. Previous studies have reported that the serum concentration of TNF‐α was increased after infliximab therapy in patients with Crohn's disease (Billiet et al, ; Candon et al, ; Cornillie et al, ; Eder et al, ; Ogawa, Matsumoto, Esaki, Torisu, & Iida, ), as well as in those with rheumatoid arthritis (RA) (Charles et al, ; Cuchacovich et al, ) and juvenile idiopathic arthritis (JIA) (Levalampi et al, ). Furthermore, the serum concentration of TNF‐α has also been shown to be positively associated with both the dose and the serum concentration of infliximab (Candon et al, ; Charles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 concentrations at baseline were higher in primary non-responders compared to responders in CD patients treated with infliximab. Multiple logistic regression identified TNF/CRP ratio at baseline as predictive for primary non-response to infliximab at week 14 ( 112 ).…”
Section: Blood Markersmentioning
confidence: 99%
“…The TNF/CRP ratio was associated with clinical response (OR 2.8 [1.4‐5.5], P = 0.003), which may underscore the contribution of TNF‐independent inflammation. An elevated IL‐8 concentration at baseline was also associated with nonresponse . Finally, a decrease in serum IL‐9 between baseline and week 14 could accurately predict both clinical remission and mucosal healing at week 30 (AUC 0.803 and 0.752 respectively) …”
Section: Resultsmentioning
confidence: 94%
“…In the absence of additional pharmacokinetic data, it remains uncertain whether these proteins reflect true nonresponders or an increased inflammatory load that requires intensified treatment to obtain adequate drug levels. Several studies have attempted to discriminate nonresponse based on TNF‐driven from TNF‐independent disease . However, biomarkers to identify true anti‐TNF nonresponse unrelated to underlying pharmacokinetics are still coveted and further research is warranted.…”
Section: Discussionmentioning
confidence: 99%